2021
DOI: 10.1016/j.jtumed.2021.05.005
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of a new paste formulation as an alternative therapeutic agent for traumatic ulcers

Abstract: Objectives The present study aims to evaluate the healing effect of a new topical paste formulation on mucosal wounds. Methods This study was conducted in 40 adult male rabbits. The animals were divided into two groups: a control group containing rabbits that were treated with only Orabase paste (comprising olive oil and beeswax) and an experimental group that included rabbits that were treated with Orabase paste containing hyaluronic acid, rosemary extract, and metroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…In this context, a pH/glucose dual-responsive metformin release hydrogel dressing with adhesion and self-healing via dual-dynamic bonding for athletic diabetic foot wound healing has been recently described by Liang et al [49]. In a different study, the efficacy of a new paste formulation as an alternative therapeutic agent for traumatic ulcers was presented [50]. In the study, conducted using 40 adult male rabbits, the new formulation was effective in resolving inflammation during specific phases of mucosal healing and improved the wound healing process at different stages.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, a pH/glucose dual-responsive metformin release hydrogel dressing with adhesion and self-healing via dual-dynamic bonding for athletic diabetic foot wound healing has been recently described by Liang et al [49]. In a different study, the efficacy of a new paste formulation as an alternative therapeutic agent for traumatic ulcers was presented [50]. In the study, conducted using 40 adult male rabbits, the new formulation was effective in resolving inflammation during specific phases of mucosal healing and improved the wound healing process at different stages.…”
Section: Discussionmentioning
confidence: 99%
“…Potential healing of rosemary essential oil was highlighted in the study of Abu-Al-Basal et al [ 57 ], where Rosmarinus officinalis essential oil reduced inflammation and wound debridement when topically applied on wounds. The study of Abid et al [ 87 ] also showed an obvious synergistic effect of hyaluronic acid, rosemary oil, and metronidazole to achieve better wound healing.…”
Section: Resultsmentioning
confidence: 99%